Impact and Resolution of Franchise Disputes: Review of Legal Cases and Alternative Dispute Resolutions for Franchise Brand Rights - Hartati, Margaret (CV. Rayyan Dwi Bharata, 2023)
This study aims to analyze the impact arising from disputes in the franchise industry, with a focus on disputes related to trademark rights deviation. In order to understand the complexity of these disputes, this study involves reviewing legal cases involving parties in franchise relationships and identifying the types of infringement that are common in relation to franchise trademark rights. In addition, this study also analyzes alternative dispute resolution that can be used to resolve conflicts between franchisees and franchisors. In this analysis, alternative dispute resolution such as mediation, arbitration and negotiation are evaluated to understand their effectiveness and suitability in the context of franchise disputes. It is hoped that the results of this research will provide in-depth insight into the impact of franchise disputes on the parties involved and identify effective dispute resolution strategies to reduce potential losses and promote healthy relationships between franchisees and franchisors.